The Overnight socialite : a novel - Clark, Bridie (New York, NY : Weinstein Books, 2009)
Set against the glittering backdrop of contemporary Manhattan, The Overnight Socialite puts a 21st-century sheen on a timeless story of transformation and unlikely love.
Keywords: Fashion designers -- Fiction; Anthropologists -- Fiction; Socialites -- Fiction; New York (N.Y.) -- Fiction